Fabrication of copper metallized titania nanoparticles via vacuum thermal evaporation - Masa, Hearty Marie B.; Onrubia, Arnold C.; Santos, Jasper Lance S.
As a smart material, the photocatalytic property of titanium dioxide or titania can be used to break down organics under exposure to ultraviolet light in this application, the large surface area provided by nanomaterials is necessary for efficient use. However, its prohibitive cost limits its widespread use; currently it is limited to optoelectronics and specially coatings. This experiment aims to produce cheap, modified titania nanoparticles whose photocatalytic property is comparable with commercial P-25 titania nanotubes. Hydrothermal method was used to produce nanoparticles for its important feature such as high melting point, very low solubility, acid resistance and inexpensive. These, while already functional, are modified by metallization, specifically with the vacuum evaporation and deposition of copper to enhance photocatalytic activity. Scanning electron microscope (SEM) is used to gauge the degree of metallization by checking particle size before and after. The effect of metallization on photocatalytic property is evaluated using a simple dark box test of the titania along with an organic indicator, methyl orange. The amount of methyl orange that is degraded over a period of time is determined using UV VIS spectrophotometry. The results obtained from using the modified titania is compared to the results obtained from using the commercial titania. This study aims to produce modified titania nanoparticles with the same efficiency as of the commercial titania in degrading organic pollutants.